Produção de bioquerosene de aviação: uma análise comparativa de diferentes processos tecnológicos - Pinheiro, Matheus Lucas (Universidade Federal de São Carlos, 2023)
In the face of growing global concern about climate change and environmental events witnessed over the past decades, there arises an urgent need to seek alternatives that minimize the impacts of human activities, particularly concerning the ongoing use of fossil fuels. The aviation sector stands as one of the largest greenhouse gas emitters worldwide, prompting efforts to mitigate its environmental footprint. One of the alternatives to reduce emissions is the production of aviation biofuel, a renewable and sustainable fuel that can partially or completely replace conventional aviation kerosene. This work aims to analyze the technological processes available in literature and certified by competent bodies, with special emphasis on regional availability of raw materials, in order to identify the potential for implementing production frameworks within the country. In the current scenario, the HEFA pathway, utilizing soybeans as a feedstock, emerges as the most promising and viable short-term alternative for aviation biofuel production, while other oilseeds also exhibit potential for exploration in the medium to long term. Consequently, with governmental support through the enactment of resolutions incentivizing the production and replacement of non-renewable fuels, Brazil could solidify its position as a major biofuel producer, thus mitigating the impacts of the burgeoning aviation market.
Aviation biokerosene production: a comparative analysis of different technological processes
Keywords: Bioqueronese; Biocombustíveis; Aviação; Rota HEFA; Matérias-primas; Biokerosene; Biofuel; Aviation; HEFA Pathway; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA